Model Perencanaan Program Komunikasi Humas Badan Pengelola Transportasi Jabodetabek Kementerian Perhubungan - Asep Rahman Umbara; Aminah Swarnawati (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
Communication planning is an essential part of a public organization such as BPTJ. In carrying out its duties and roles, BPTJ Public Relations is required to develop appropriate communication plans based on the stages carried out to achieve the main objectives of the PR communication program itself, namely building opinions and changing behavior. The purpose of this study was to identify and analyze the planning stages of the BPTJ Public Relations communication program, the model run by BPTJ Public Relations, and the challenges and obstacles in carrying out communication program planning. The theory used is the Assifi and French communication planning, model. This study uses a qualitative descriptive method with data collection techniques through in-depth interviews and literature studies. Based on the results of the research, it can be interpreted that BPTJ Public Relations has carried out the planning communication stages from problem analysis to evaluation. The Assifi and French models have been implemented by BPTJ Public Relations and have challenges and obstacles both internal and external to the organization. The recommendation of this research is that BPTJ Public Relations must have a standard concept of a communication plan, be consistent in terms of visual appearance on social media such as corporate color and optimize public figures as communicator.